VD_FINDINFO HC / 2013 / 182 vom 26. Februar 2013 - VD Tribunal cantonal (2013)
DROIT D'ÊTRE ENTENDU, CITATION À COMPARAÎTRE, NOTIFICATION IRRÉGULIÈRE | 29 al. 2 Cst., 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 68 al. 3 CPC (CH)